Diglossia in the Caribbean: the current situation of Saint Kitts (Islas, 2023)
Introduction: The study of Creole on the Caribbean island of St. Kitts is essential, since the basic characteristics of Creole have not been studied. This article aims to determine, from a sociolinguistic perspective, the functional characteristics of Creole currently spoken on the island.Methods: We worked with a sample of 20 native informants of the island and applied questionnaire techniques on attitudes and realities of contexts where Creole is or is not used. The linguistic attitudes of Creole and the variables gender, age and level of education were taken as fundamental elements.Results: It was found that there is a negative attitude towards Creole, which gives rise to a situation of marked diglossia in favor of English. On the other hand, certain modifications were observed at all levels, which demonstrates the existence of Creole and the need to create a language policy that attenuates the diglossia in favor of English.Conclusions: A current contradiction is evident as a result of centuries of linguistic struggle: Creole, on the one hand, is used in orality and in popular traditions such as songs, jokes and stories, in the street and in domestic settings, on the other hand, it is externally rejected in «cultured» settings and considered of lesser linguistic and social value.
Keywords: caribbean creole; diglossia; languages in contact